IMPLEMENTASI KEBIJAKAN TAMBAHAN PENGHASILAN PEGAWAI APARATUR SIPIL NEGARA PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI KALIMANTAN BARAT - Lisa, Yuliana (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
The title of this research is: Implementation of the Additional Income Policy to Civil Servants at the Secretariat of the Regional House of Representatives (DPRD) of West Kalimantan Province. The problem was caused by the small amount of money that the local government offered to fund extra income of the Secretariat staff and by the complicated, time-consuming administrative process of applying and receiving the additional income. This study aims to describe and analyze the process of implementing the additional income policy to Civil Servants at the Secretariat of the Regional House of Representatives (DPRD) of West Kalimantan Province, through the stages of organization, interpretation, and application. The results indicate that the implementation process consists of three stages. The organizational or institutional level has not yet completely alluded to the standards of the policy since some Civil Servants still seem to lack work discipline. The understanding of the Civil Servants about the policy is low, which is the interpretation stage. The implementation phase has been implemented but not in the best way and is not fully in line with West Kalimantan Governor Regulation No. 2 of 2023. It is recommended that the concerned agencies should improve outreach, technical knowledge, and standardized SOPs.